An assessment of rice seed quality at various physiological harvest maturity stages / Abdul Rahman Ansori and Siti Maslizah Abdul Rahman - Ansori, Abdul Rahman; Abdul Rahman, Siti Maslizah (Universiti Teknologi MARA Cawangan Pahang, 2021)
The utilization of good quality seeds enhances crop yield. Present study aims to determine the effect of different physiological harvest maturity stages on seed quality of Indica rice cv. MR220. Rice seed (cv. MR 220) sample was collected from a paddy field in Bukit Lintang, Melaka, Malaysia and was harvested at three different stages of physiological maturity at 104, 111, and 118 days after sowing (DAS). The parameters studied were the initial seed moisture content (MC), electrical seed conductivity (EC), 1000 seeds fresh weight (SFW) and, germination capacity (GC). The seeds’ MC at 104 DAS was 17.1%, 111 DAS was 14.33% and 118 DAS was 13.34%. Thousand SFW obtained the highest yield (32.72g) for the earliest harvest maturity (104 DAS) followed by 111 DAS (29.02g), and 118 DAS (27.42g). Seed leachate for the harvested seed at 104 DAS significantly recorded the highest by 0.033 μs cm-1g-1, as compared to only 0.012 μs cm-1g-1 for 111 and 118 DAS. Germination capacity (%) for both 118 and 114 DAS incurred more than 85% and a lower percentage (77%) was recorded from 104 DAS. In conclusion, loss of seed quality depends on physiological maturity whereas the sooner the harvest date, the lower the seed quality obtained. Therefore, farmers need to avoid early harvesting. The physiological maturity between 111 to 118 DAS is suggested to be an ideal range for farmers to produce better quality rice seeds of cv. MR220.